Perceived donor trust, managerial competence and financial accountab ility in non governmental organisations in Uganda - Katumba, Connie (Kampala, 2013)
Unpublished thesis (Msc. ACC&FIN) - Makerere University, 2013.
Includes bibliographical references.
Keywords: Non-governmental organisations -- Accounting -- Uganda; Finance, Public -- Accounting -- Uganda